2023
DOI: 10.1177/1098612x231194460
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study and outcome of 307 cats with feline infectious peritonitis treated with legally sourced veterinary compounded preparations of remdesivir and GS-441524 (2020–2022)

Samantha S Taylor,
Sally Coggins,
Emi N Barker
et al.

Abstract: Objectives Feline infectious peritonitis (FIP) is a serious disease that arises due to feline coronavirus infection. The nucleoside analogues remdesivir and GS-441524 can be effective in its treatment, but most studies have used unregulated products of unknown composition. The aim of the present study was to describe the treatment of FIP using legally sourced veterinary-prescribed regulated veterinary compounded products containing known amounts of remdesivir (injectable) or GS-441524 (oral tablets). Methods C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 66 publications
3
13
0
1
Order By: Relevance
“…Two cats in this study received a novel antiviral therapy 8,9,12,13,20 and follow-up US showed partial to complete resolution of changes, suggesting that US may be a valuable tool in assessing response to treatment with this trial drug. Persistent US changes despite curative treatment with antiviral therapy have been documented in cats with FIP.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Two cats in this study received a novel antiviral therapy 8,9,12,13,20 and follow-up US showed partial to complete resolution of changes, suggesting that US may be a valuable tool in assessing response to treatment with this trial drug. Persistent US changes despite curative treatment with antiviral therapy have been documented in cats with FIP.…”
Section: Discussionmentioning
confidence: 77%
“…Persistent US changes despite curative treatment with antiviral therapy have been documented in cats with FIP. 9,12 Hence, a better understanding of FIP lesions that are detectable with ultrasound pretreatment is beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is indicative of high viral loads, but must be validated through quantification. Furthermore, a relatively high percent (Supplementary Table 4) of confirmed cases in Cyprus was presented with neurological signs (28%), which is double of what would be expected with classical FIP (14%) 27 . This may be due to increased awareness of presentation or be inherent to FCoV-23 neurotropism; however, further investigation is required.…”
Section: Discussionmentioning
confidence: 82%